Terapia Cognitivo-Conductual En El Tratamiento Para El Consumo De Sustancias En Adultos - Loaiza Castillo, Junior Vinicio (2024)
Substance addiction has caused multiple challenges, ranging from the personal and psychological to the social aspect, even affecting public health. This problem manifests itself in high levels of individual and physical developmental impairment, as well as a significant decrease in the quality of life for those who suffer from it. Given the urgency of addressing this problem, it is crucial to disseminate the benefits of cognitivebehavioral therapy, as these can effectively contribute to the control and mitigation of addiction. Therefore, this study was conducted with the aim of demonstrating scientific evidence of Cognitive Behavioral Therapy (CBT) for the treatment of substance use in adults. The methodology applied comprised the design of a bibliographic and descriptive study, working with a sample of 25 scientific articles, and published in the digital journals Google Scholar, Pubmed, Dialnet, Sciencie Direct. The 25 selected scientific studies met the previously established inclusion and exclusion criteria, which were screened and processed using the PRISMA diagram. The results revealed that among the risk factors that influence substance use are family problems, loneliness, specific personality traits, depression and peer pressure, while the most commonly used substances are tobacco, alcohol, cannabis and cocaine, Therefore, information should be promoted on the implementation of strategies to face diverse situations and what cannot be lacking in the treatment of abuse in the consumption of these substances, which led to the conclusion that it is important to promote the contribution of cognitive behavioral therapy to counteract this problem that affects the psychological health of consumers to promote a better lifestyle